Prevalence of traditional eye medicine and self-treatment in Gurage Zone, Rural Ethiopia - Sadik Taju Sherief; Munira Sherefedin Sitotaw; Abonesh Girma (BMC, 2024)
Abstract Introduction Traditional medicines are commonly used worldwide, especially in Africa-however, there is limited information on the prevalence and types of traditional eye medicine utilization in Ethiopia. The goal of this study was to determine the prevalence, the type and nature of traditional eye medicine use and practices related to self-medication for ophthalmic diseases in a rural Ethiopian population. Methods A cross-sectional study was conducted in six randomly selected primary health centers in rural Gurage Zone, Southern Ethiopia. Health-seeking behavior, use of self-medication, and traditional eye medicine were assessed in the population using a semi-structured questionnaire. Descriptive statistics and multivariable logistic regression analysis were computed to determine associated factors for using self-medication and traditional eye medicine. Result Of the 814 participants interviewed, 487 (59.8%) reported using traditional eye medicine, mainly for combinations of symptoms of ocular redness, irritation, and eye discharge (95.5%). Besides, 604 (74.2%) participants reported self-treatment with tetracycline 1% eye ointment. Older age, females, low income, no formal education, and lack of access to media were risks for utilizing traditional eye medicine. Conclusion The use of traditional eye medicine and self-treatment are common in this population. Regulatory legislation, public awareness, and making eye care are vital activities required to monitor such practices.